KELAS SOSIAL DAN PANDANGAN DUNIA PENGARANG NOVEL KEOK KARYA PUTU WIJAYA - Kadaryati Kadaryati (p-ISSN 2356-0576, 2019)
Abstract: The research main goal is to describe the genetical structure as the reconstruct of the social novel Keok by Putu Wijaya includes social classes and the world sight of the author. The connection between both aspect caused by the social condition before and after new order. A group of authors show up as subjects with high confidence in responding the cultural social situation based on the new world side this condition reflects that there is conflict among the author in refusing the traditional system and catching new value system. Keywords: genetical structure, reconstruct of the social, novel Abstrak: Penelitian  ini bertujuan untuk mendeskripsikan strukturalisme genetik sebagai rekonstruksi sosial novel Keok karya Putu Wijaya  meliputi kelas sosial dan pandangan dunia pengarangnya. Hubungan antara keduanya disebabkan adanya kondisi sosial menjelang dan sesudah Orde baru. Kelompok pengarang tampil sebagai subjek penuh percaya diri dalam menanggapi situasi sosial budaya berdasarkan pandangan dunia baru. Keadaan ini mencerminkan adanya pergulatan pengarang penolakan sistem tradisional dan menjaring sistem nilai baru.Kata kinci: struktural genetic, rekonstruksi social, novel